Pengaruh Arus Kas Operasi Dan Laba Akuntansi Terhadap Return Saham Pada Perusahaan Manufaktur Sub Sektor Kontruksi Bangunan - Desi Aramana (Jurnal Akuntansi dan Keuangan Kontemporer (JAKK), 2020)
In the globalization era, the capital market plays an important role for the economic progress of a country. The building construction industri is one sektor that attracts investor’s attention where the facts show that this sektor is very promising. This study aims to determine the effect of operating cash flow and accouting profit on stock return in a building construction industry manufacturing company listed on the Indonesian stock exchange. The research sample is a company in the bulding construction industry sector which was recorded in 2014-2018, which amounted to 6 companies. The method of analysis in this study uses purposive sampling. The resultsof the study show that operating cash flows have a significant effect on stock returns, while a accounting profits do not effect stock returns. The results indicate that operating cash flows have an impact on the stock market, especially influencing the return of funds invested in the building construction industry.